Development education the Philippine experience - Mendoza, Rene L.; Rosas, Nilo L.
Development education efforts in the Philippines are much too diversified to be controlled or handled solely by the academe, nor by the Ministry of Education and Culture. This weakness of decentralization may in fact be the source of its strength, the lack of a centralized controlling structure or figure would in fact create the greatest need for internalizing the goals and directions of development education.
Revised and lengthened version of a concept paper originally written for presentation at the United Nations Educational, Scientific and Cultural Organization (UNESCO) meeting in Bangkok, March 1982.
Keywords: Education -- Curricula -- Philippines; Universities and colleges -- Curricula -- Philippines; Education ans state -- Philippines